2008
DOI: 10.1159/000128275
|View full text |Cite
|
Sign up to set email alerts
|

Proton Spectroscopy in Alzheimer’s Disease and Cognitive Impairment No Dementia: A Community-Based Study

Abstract: Objective: To describe the findings of proton magnetic resonance spectroscopy (1H-MRS) in Alzheimer’s disease (AD) and cognitive impairment, no dementia (CIND) elderly from a community-based sample. Methods: Thirteen patients with AD, 12 with CIND and 15 normal individuals were evaluated. The 1H-MRS was performed in the right temporal, left parietal and medial occipital regions studying the metabolites N-acetylaspartate (NAA), creatine (Cr), choline (Cho) and myoinositol (mI). The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
0
13
1
Order By: Relevance
“…A previous study using MR spectroscopy performed on both anterior and posterior cingulate gyri showed that the NAA/Cr and mI/Cr of posterior cingulate gyri were correlated with cognitive test scores and those of anterior cingulate gyri were correlated with BPS scores [21]. In this study, only the mI/Cr showed a significant correlation while the NAA/Cr of the posterior and the anterior cingulate gyri was not correlated with both cognitive dysfunction and BPS.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…A previous study using MR spectroscopy performed on both anterior and posterior cingulate gyri showed that the NAA/Cr and mI/Cr of posterior cingulate gyri were correlated with cognitive test scores and those of anterior cingulate gyri were correlated with BPS scores [21]. In this study, only the mI/Cr showed a significant correlation while the NAA/Cr of the posterior and the anterior cingulate gyri was not correlated with both cognitive dysfunction and BPS.…”
Section: Discussioncontrasting
confidence: 49%
“…These varying results may be attributable to the different patient groups examined in each study. For example, community-based studies have shown that the NAA/Cr ratio in MCI was almost the same when compared to a normal control group [21,22]. On the other hand, a clinic-based study showed that the NAA/Cr ratio in an MCI group who became demented after a 1-year follow-up decreased when compared to a normal control group [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, examined using levels of multiple metabolites within the same hippocampal VOI, Rupsingh et al (2011) found that the accuracy of discriminating clinical AD from HC was 71% using NAA / Cr , 80% using Glu , and 94% using a combination of the quantitative NAA / Cr , Glu , and mI [102]. Similarly, in the study by Wang and others (2009), the increased mI / NAA in AD in both hippocampal and posterior cingulate VOIs was used for AD and HC classification; a better performance was obtained than when using data from a single VOI [116], as also reported by Azevedo and colleagues (2008) using a lower field [127]. These observations linked the uneven spatial expression to progressive distortion of brain structures compromised by the disease [11], suggesting some potential of MRS-based evaluation of multiple neurochemicals, and of combining metabolite data acquired from more than one brain region.…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, combining metabolite data from different VOIs can improve AD identification [116], so too with combining information of multiple metabolites [102, 127, 136]. The performance of MRS can be further improved when data are combined with multimodal neuroimaging data and clinical assessment data [128-130].…”
Section: Discussionmentioning
confidence: 99%
“…Azevedo, D. et.al. [37] have studied proton spectroscopy in Alzheimer's disease and cognitive impairment no dementia . They have confirmed on the basis of proton magnetic resonance spectroscopy the hypothesis metabolic alterations are present .…”
Section: Jardetzky Omentioning
confidence: 99%